Factors associated with acute respiratory infection in children under the age of 5 years: evidence from the 2011 Ethiopia Demographic and Health Survey - Gebertsadik A; Worku A; Berhane Y (Dove Medical Press, 2015)
Achamyelesh Geberetsadik,1 Alemayehu Worku,2 Yemane Berhane3 1School of Public and Environmental Health, Hawassa University, Hawassa, 2School of Public Health, Addis Ababa University, 3Addis Continental Institute of Public Health, Addis Ababa, Ethiopia Background: Acute respiratory tract infection (ARI) remains the major cause of child mortality in Sub-Saharan Africa. Various factors are associated with its occurrence and vary by context. However, available large-scale, population-based data are not fully exploited to identify locally relevant risk factors. The objective of this study was to identify factors associated with ARI in children under the age of 5 years in Ethiopia.Methods: Further analysis of the 2011 Ethiopia Demographic and Health Survey was carried out involving 11,645 children under the age of 5 years and their mothers. Information relevant to the current study was extracted from the main data set and a working data set was prepared. A complex survey logistic regression analysis was applied.Results: Acute ARI in this study was associated with severe malnutrition. Children who were severely wasted were highly likely to develop ARI (adjusted odds ratio [AOR] 1.7; 95% confidence interval [CI] 1.1–2.5). ARI was less likely to occur in children from families with an educated father and professional mother (AOR 0.4; 95% CI 0.2–0.6 and AOR 0.1; 95% CI 0.01–0.6, respectively).Conclusion: Malnourished children from a lower socioeconomic category are more likely to suffer from ARI. Targeting disadvantaged children for effective interventions can help reduce the burden of morbidity and death due to ARI. Keywords: acute respiratory tract infection, pneumonia, severe malnutrition, children, Ethiopia